Searches for sterile neutrinos with the IceCube detector - Aartsen, M; Abraham, K; Ackermann, M; Adams, J; Aguilar, J; Ahlers, M; Ahrens, M; Altmann, D; Andeen, K; Anderson, T; Ansseau, I; Anton, G; et al. (American Physical Society, 2016)
The IceCube neutrino telescope at the South Pole has measured the atmospheric muon neutrino spectrum as a function of zenith angle and energy in the approximate 320 GeV to 20 TeV range, to search for the oscillation signatures of light sterile neutrinos. No evidence for anomalous ν_{μ} or ν[over ¯]_{μ} disappearance is observed in either of two independently developed analyses, each using one year of atmospheric neutrino data. New exclusion limits are placed on the parameter space of the 3+1 model, in which muon antineutrinos experience a strong Mikheyev-Smirnov-Wolfenstein-resonant oscillation. The exclusion limits extend to sin^{2}2θ_{24}≤0.02 at Δm^{2}∼0.3  eV^{2} at the 90% confidence level. The allowed region from global analysis of appearance experiments, including LSND and MiniBooNE, is excluded at approximately the 99% confidence level for the global best-fit value of |U_{e4}|^{2}.